Implementation of Life-Support Plantation Partnership Area Management Policy of PT. Bumi Mekar Hijau And Farmers Association (Gapoktan) Riding Bersatu In Riding Village, Ogan Komering Ilir District, South Sumatera Province - Deni Priatna Priatna; Rujito Agus Suwignyo; Ardiyan Saptawan (Sriwijaya Journal of Environment, 2020)
Management of life-support plantation partnership area held by PT. BMH and Farmers Association (Gapoktan) Riding Bersatu had not yet effective because the management realization and community’s welfare had not yet improved. The purpose of this research was to analyze policy implementation effectiveness and arrange policy strategy to increase the realization of life-support plantation partnership area management. Unsuccessful program was influenced by program which did not successfully achieve the given benefit. In addition, program executor did not have agroforestry activity capability; executor’s commitment, and executor’s power, interest, also strategy in implementing agroforestry activity were not considerably play a role in realizing the success of the program. All stakeholders’ obedience and response also became an extremely important thing. If policy content variable did not reach the determined target, the program implementation would not generate optimal result. Therefore, strategy performed to optimize the program was by synchronizing policy content with the policy context in integrated policy system.